Prediction of novel pluripotent proteins involved in reprogramming of male Germline stem cells (GSCs) into multipotent adult Germline stem cells (maGSCs) by network analysis. (October 2018) - Guttula, Praveen Kumar; Agarwal, Anushka; Maharana, Usharani; Gupta, Mukesh Kumar
Graphical abstract: Highlights: Various proteins such as Pou5f1 and Prdm14 are involved in the Germline stem cell maintenance. Five Identified clusters were ranked according to the score. Lama3, Lamc2, and Lama1 in cluster 4 involve in the P13K-Akt signaling pathway plays an important role in pluripotency. Abstract: Germline stem cells (GSCs) are known to transmit genetic information from parents to offspring. These GSCs can undergo reprogramming to transform themselves into pluripotent stem cells, called as Multipotent adult Germline stem cells (maGSCs). The mechanism of the reprogramming of GSCs to maGSCs is elusive. To investigate novel factors that may govern the process of reprogramming, the RNA-seq data of both GSCs and maGSCs were retrieved and subjected to Tuxedo protocol using Galaxy server. Total 1558 differentially expressed genes were identified from the analysis. Protein sequence in the FASTA format of all 1558 differentially expressed genes was retrieved and submitted to Pluripred web server to predict whether the proteins were pluripotent or not. A total of 232 proteins were predicted as pluripotent, and to identify the novel proteins, these were submitted to STRING database to obtain an interaction map. The obtained interaction map was submitted to Cytoscape, and various apps such as MCODE and Centiscape were used to identify the clusters and centrality measures between the nodes of the generated network. Five clusters were identified and ranked according to their score. Novel pluripotent proteins like cadherin related cdh5, cdh10 were predicted. Phox2b, Nrp2, Dll1, Shh, Gbx2, Nodal, Lefty1, Wnt7b, Pitx2, fgf4, Pou5f1, Nanog, Tet1, trim8, alx2, Dppa2, Prdm14, Sox11, Esrrb were predicted to be involved in the stem cell development. Dppa2, Sox11, Sox2, Bmp4, Shh, and Otp were predicted to be involved in positive regulation of the stem cell proliferation. Pathway analysis further revealed that signaling pathways such as Wnt, Jak-Stat and PI3K may play important role in the pluripotency of the maGSCs. Novel proteins involved in pluripotency, which were predicted by our findings, can be experimentally researched in future.